ETHICS EDUCATION IN RELIGIOUS EDUCATION. ANALYSIS OF THE MAJOR ORIENTATIONS FOUND IN ENGLAND’S NATIONAL FRAMEWORK FOR RELIGIOUS EDUCATION - Bouchard, Nancy (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2020)
This paper presents an innovative analytical model of Ethics Education, and uses it to analyze the major learning components found in England’s National framework for religious education (NFRE). The model includes seven components: three simple ones – Education for Society (ES), Personal Identity (PI), Education for Otherness (EO) – and four interwoven ones (PI/EO, PI/ES, EO/ES and PI/EO/ES). Our results from the analysis of the NFRE show a strong concentration of PI and EO components in its learning goals, and validates the model of Ethics Education developed in French-speaking context.